PERANAN SISTEM INFORMASI MANAJEMEN UNTUK PENGAMBILAN KEPUTUSAN PENGUSAHA KECIL - Utami, Setyaningsih Sri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
Abstract Management Information System is a system of human/machine unified (integrated) to present information that supports the functions of the operation, management and decision making within an organization. The system uses software, hardware computer, procedure guidelines, models and management decisions and a data base. Management Information System based computer system is useful both in closed and open systems. In the decision model is closed, the computer acts as a counter to calculate the optimum results. In the open model, the computer acts as a helper for human decision makers to calculate, store, looking back, analyze the data and so on. The design allows the human decision makers to allocate tasks for himself or on the computer. Management Information System is a set of indispensable information tool by small scale industries/small entrepreneurs to overcome the problems encountered. With the growing role of the Management Information System can finally taken advantage of the special characteristics of successful managers of small firms. Keywords: Management Information Systems, software, hardware, small firms